Health and survival of young children in southern Tanzania - Ketende Sosthenes; Mushi Adiel K; Mbuya Conrad; Shirima Kizito; Manzi Fatuma; Mrisho Mwifadhi; Armstrong Schellenberg Joanna RM; Alonso Pedro L; Mshinda Hassan; Tanner Marcel; Schellenberg David (BMC, 2008)
Abstract Background With a view to developing health systems strategies to improve reach to high-risk groups, we present information on health and survival from household and health facility perspectives in five districts of southern Tanzania. Methods We documented availability of health workers, vaccines, drugs, supplies and services essential for child health through a survey of all health facilities in the area. We did a representative cluster sample survey of 21,600 households using a modular questionnaire including household assets, birth histories, and antenatal care in currently pregnant women. In a subsample of households we asked about health of all children under two years, including breastfeeding, mosquito net use, vaccination, vitamin A, and care-seeking for recent illness, and measured haemoglobin and malaria parasitaemia. Results In the health facility survey, a prescriber or nurse was present on the day of the survey in about 40% of 114 dispensaries. Less than half of health facilities had all seven 'essential oral treatments', and water was available in only 22%. In the household survey, antenatal attendance (88%) and DPT-HepB3 vaccine coverage in children (81%) were high. Neonatal and infant mortality were 43.2 and 76.4 per 1000 live births respectively. Infant mortality was 40% higher for teenage mothers than older women (RR 1.4, 95% confidence interval (CI) 1.1 - 1.7), and 20% higher for mothers with no formal education than those who had been to school (RR 1.2, CI 1.0 - 1.4). The benefits of education on survival were apparently restricted to post-neonatal infants. There was no evidence of inequality in infant mortality by socio-economic status. Vaccine coverage, net use, anaemia and parasitaemia were inequitable: the least poor had a consistent advantage over children from the poorest families. Infant mortality was higher in families living over 5 km from their nearest health facility compared to those living closer (RR 1.25, CI 1.0 - 1.5): 75% of households live within this distance. Conclusion Relatively short distances to health facilities, high antenatal and vaccine coverage show that peripheral health facilities have huge potential to make a difference to health and survival at household level in rural Tanzania, even with current human resources.